Analysis of Handoff Communication Using SBAR (Situation, Background, Assessment, Recommendation) in Emergency Department and Intensive Care Unit: A Scoping Review - Azmi, Nur; Prawesti Priambodo, Ayu; Nuraeni, Aan (Journal of Health and Nutrition Research, 2025)
Communication between health workers is crucial in providing nursing care and improving patient safety. Communication problems can cause incidents that lead to disability or death. This study aimed to identify the implementation of handoff communication using sbar in the emergency department and intensive care unit. This review used a scoping review design that uses the Arksey and O'Malley framework. Article searches through two databases, namely Sciencedirect and Pubmed, and the search engine, Google Scholar. The keywords used were "Health workers or Healthcare professionals AND SBAR implementation or SBAR or Handoff Communication AND Emergency rooms or Emergency departments AND Intensive Care Unit". There were nine articles that fulfilled the inclusion criteria and were analyzed in this study. The results of the review showed that the description of the implementation of handoff or SBAR communication, studies showed variations in the effectiveness of its implementation in various countries and health settings. There are several factors that influence the implementation of SBAR and the implementation of handoff, namely work experience, attitudes, knowledge, and formal training. Implementation of handoff communication and SBAR still shows substansial challenges, both in terms of effectiveness and quality. Although SBAR has been widely recognized as an effective tool to improve communication, its implementation is uneven across countries and health settings. SBAR implementation is often disrupted by factors such as external interference, lack of training, or incomplete information conveyed during the handover process, which ultimately affects patient safety.